Hodin : Rétromorphing. - Hodin, Jean Marie; Robette-Papet, Gérard (Le Touquet, 2003)
L'exposition est consacré aux 30 années de création artistique de Hodin.
biog., coll. [3 p.]
Duits
Engels
Frans
Nederlands
Spaans
Keywords: Hodin, Jean Marie